The resulting equation after substitution is
5x + 4(-2x + 6) = 3
quite literally you replaced y with what it equals (as said in the second equation)
you then distribute the 4 within the parenthesis
5x + -8x + 24 = 3
You make it easier
5x - 8x +24 = 3
you combine like terms
-3x + 24 = 3
you subtract 24 from both sides
-3x = -21
you divide both sides by -3
meaning x = 7
you then use that value x = 7 and substitude it for the x in the other equation.
That makes the y equation
y = -2(7) + 6
you then solve
y = -14+6
y = 6 - 14
y = -8